The Leadership Portfolio Program at The University of Pittsburgh: Teaching leadership to graduate students1. Issue 3 (October 2019) - Kearns, Kevin
The Graduate School of Public and International Affairs, University of Pittsburgh provides an extra-curricular leadership development experience called the Leadership Portfolio Program. The Leadership Portfolio Program uses both classroom and community-based experiences to develop and refine leadership skills in graduate students who are preparing for careers in public service. This article describes the Leadership Portfolio Program and, based on student feedback, offers insights on pedagogical strategies for teaching leadership to pre-service students.